"Clip-Stone" Filiation Within the Biliary Tract. Issue 3 (1993) - Mansvelt, B.; Harb, J.; Farkas, B.; Mourou, M.; Huguet, C.
Abstract : A case of cholangitis due to the migration of a metal clip used for surgical cholecystectomy 4 years earlier, is reported. The diagnostic approach and therapeutic options, either endoscopic or surgical are discussed. The use of resorbable clips during the performance of laparoscopic cholecystectomy should avoid this type of complication.